PERAN KH. M. HASYIM ASY’ARI DALAM TRANFORMASI PENDIDIKAN DI PESANTREN TEBUIRENG JOMBANG - Hidayah, Yuli Lailatul; Supratno, Haris (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2024)
KH. Hasyim Asy'ari played an important role in the transformation of Islamic boarding school education, especially at the Tebuireng Jombang and in general in Indonesia. This research will discuss the role of KH. M. Hasyim Asy'ari in the transformation of Islamic boarding school education, implementation at the Tebuireng Jombang, and his role in the educational transformation at the Tebuireng Jombang. This research uses a qualitative field phenomenology approach, focusing on the experience of the resource persons related to the transformation of Islamic boarding school education, as well as observation and documentation works left by KH. M. Hasyim Asy'ari. Based on the research results, it can be concluded that KH. M. Hasyim Asy'ari has an important role in the transformation of Islamic boarding school education, especially at the Tebuireng and in general in Islamic education in Indonesia. The process of implementing educational transformation at the Tebuireng goes through three stages: the Salaf period, the initial period of introducing general/non-religious material, and the khalaf/modern period until now. Even though it follows the times, Islamic boarding school education still maintains its characteristics as a place for Islamic religious education with a balance of religious and general material adapted to the context of each Islamic boarding school.